Applied Machining Technology - Tschätsch, Heinz (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Machining and cutting technologies are still crucial for many manufacturing processes. This reference presents all important machining processes in a comprehensive and coherent way. It provides the practising engineer with many technical information of the manufacturing processes and collects essential aspects such as maximum obtainable precision, errors or reference values. Many examples of concrete calculations, problems and their solutions illustrate the material and support the learning reader. The internet addresses given in the appendix provide with a fast link to more information sources.